2015
DOI: 10.1186/s12951-014-0061-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of scanning near field optical imaging to the study of human sperm morphology

Abstract: BackgroundThe morphology of spermatozoa is a fundamental aspect to consider in fertilization, sperm pathology, assisted reproduction and contraception. Head, neck, midpiece, principal and terminal part of flagellum are the main sperm components to investigate for identifying morphological features and related anomalies. Recently, scanning near-field optical microscopy (SNOM), which belongs to the wide family of nanoscopic techniques, has opened up new routes for the investigation of biological systems. SNOM is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(51 reference statements)
2
5
1
Order By: Relevance
“…Although SNOM has been shown to reveal cytoplasmic structures in previous studies 12 , the SNOM-IR-FEL images obtained in this study were difficult to interpret in terms of structures. This was due to the use of a cleaved fibre for the SNOM imaging, which added significant tip artefacts to the topographical image and often off-set the topographic from the transmission images.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Although SNOM has been shown to reveal cytoplasmic structures in previous studies 12 , the SNOM-IR-FEL images obtained in this study were difficult to interpret in terms of structures. This was due to the use of a cleaved fibre for the SNOM imaging, which added significant tip artefacts to the topographical image and often off-set the topographic from the transmission images.…”
Section: Discussioncontrasting
confidence: 63%
“…SNOM has been used to investigate the localisation of molecules within cell membranes of prostate cancer cells 11 . Further research demonstrated SNOM can accurately define both the cell surface and internal structures in both healthy and anomalous sperm, including the acrosome, nucleus and the organisation of mitochondria 12 , and has demonstrated potential for single molecule imaging 13 . The application of SNOM to oesophageal cancer tissue studies provided evidence of its potentiality for cancer diagnosis 8 .…”
mentioning
confidence: 99%
“…With this technique peculiar structural features of these cells have been disclosed without staining procedures. As shown in Figure 3, the helicoidal organization of mitochondria in the midpiece region is well discernible in normal spermatozoa [94], and other structural features of healthy and anomalous spermatozoa are detected, all well resembling those observed in transmission electron microscopy images [95]. These works demonstrate the ability of SNOM to visualize inner cellular compartments with a typical contrast (transmission and reflection) for standard microscopy but with a higher resolution [94,95].…”
Section: Inner Cellular Organization Of Spermatozoasupporting
confidence: 63%
“…It is seen that assisted reproduction using spermatozoa with deformities not only leads to lower fertilization and pregnancy rates, but also imposes higher risk of lesions in fetal DNA (Nikbakht & Saharkhiz, ). Recently, nanoscopic techniques are being devised to describe structural details of spermatozoa (Andolfi et al, ). Taking into account the enormous prognostic value attributed to sperm morphology in assisted reproduction, we delved into this aspect in depth.…”
Section: Discussionmentioning
confidence: 99%